Optic nerve sheath meningiomas: prevalence, impact, and management strategies - Parker, Richard T (Eye Brain, 2018)
Optic nerve sheath meningiomas are rare benign neoplasms of the meninges surrounding the optic nerve. They are a significant cause of morbidity. While the mortality rate is practically zero, these tumors can blind or disfigure patients. Given that the clinical course can be variable, and treatment has the capacity to cause morbidity itself, the management of these patients can be difficult. We review the literature to discuss the prevalence of optic nerve sheath meningiomas, the association with neurofibromatosis type 2, natural history, and management options and strategies.